Optic nerve head abnormalities in nonpathologic high myopia and the relationship with visual field - Jiang, Jingwen; Song, Yunhe; Kong, Kangjie; Wang, Peiyuan; Lin, Fengbin; Gao, Xinbo; Wang, Zhenyu; Jin, Ling; Chen, Meiling; Lam, Dennis S. C.; Weinreb, Robert N.; Jonas, Jost B.; et al. (Asia-Pacific journal of ophthalmology, 2023)
Purpose: - To describe the optic nerve head (ONH) abnormalities in nonpathologic highly myopic eyes based on swept-source optical coherence tomography (OCT) and the relationship with visual field (VF). - Design: - Secondary analysis from a longitudinal cohort study. - Methods: - Highly myopic patients without myopic maculopathy of category 2 or higher were enrolled. All participants underwent a swept-source OCT examination focused on ONH. We differentiated between 3 major types (optic disc morphologic abnormality, papillary/peripapillary tissue defect, and papillary/peripapillary schisis) and 12 subtypes of ONH abnormalities. The prevalence and characteristics of ONH abnormalities and the relationship with VF were analyzed. - Results: - A total of 857 participants (1389 eyes) were included. Among the 1389 eyes, 91.86%, 68.61%, and 34.92% of them had at least 1, 2, or 3 ONH abnormalities, respectively, which corresponded to 29.55%, 31.79%, and 35.67% of VF defects, respectively. Among the 12 subtypes of the 3 major types, peripapillary hyperreflective ovoid mass-like structure, visible retrobulbar subarachnoid space, and prelaminar schisis were the most common, respectively. Perimetric defects corresponding to OCT abnormalities were more commonly found in eyes with peripapillary retinal detachment, peripapillary retinoschisis, and peripapillary hyperreflective ovoid mass-like structure. Glaucoma-like VF defects were more common in eyes with deep optic cups (28.17%) and with optic disc pit/pit-like change (18.92%). - Conclusions: - We observed and clarified the ONH structural abnormalities in eyes with nonpathologic high myopia. These descriptions may be helpful to differentiate changes in pathologic high myopia or glaucoma.